Lipschutz ulcer associated with mixed EBV/CMV infection in a 16-year-old girl. - Ozuguz, P.; Kacar, S.D.; Asık, G.; Kocoglu, T. (European Journal of Pediatric Dermatology, 2013)
The etiopathogenesis of Lipschutz's ulcer (LU) is not fully understood. Epstein-Barr virus (EBV) infection may rarely be associated with genital ulcers (ulcus vulvae acutum), a very painful manifestation. The diagnosis is made by exclusion after ruling out sexually transmitted diseases, autoimmune causes, trauma and other etiologies of genital ulcerations. Here was reported a 16-year-old adolescent female with a large and deep genital ulcer associated with acute EBV and CMV infection. The diagnosis was supported by the clinical symptoms, mild elevated circulating levels of liver enzymes and positive EBV and CMV serology. After a supportive treatment, the ulcers healed within one month. This case represents a rare important differential diagnosis of genital ulceration.